Website Analysis as a Media for Healthy Living Digital Campaign - L Wulantika; A Ragatodi; M A Sya'bani; R Nugraha (Universitas Komputer Indonesia, 2021)
A website is a collection of information or a collection of pages commonly accessed via the internet. One of them is the Healthy Living Campaign Website. This research aims to support the community in carrying out a healthy lifestyle by providing information to implement a healthy lifestyle. However, the source of information from the Healthy Living Campaign Website is said to be incomplete. For that, a maximum evaluation is needed. The research used descriptive and qualitative analysis methods. The results obtained indicate that the Healthy Living Campaign Website has advantages and disadvantages in terms of information. This result research is The Healthy Living Together Activity Website has several views in its design. It is due to several factors, such as the views that influence the design of the website. However, in general, the positive impact could be related to the information conveyed through the Healthy Living Campaign Website.